2015
DOI: 10.1186/s12859-015-0478-3
|View full text |Cite
|
Sign up to set email alerts
|

Removing batch effects from purified plasma cell gene expression microarrays with modified ComBat

Abstract: BackgroundGene expression profiling (GEP) via microarray analysis is a widely used tool for assessing risk and other patient diagnostics in clinical settings. However, non-biological factors such as systematic changes in sample preparation, differences in scanners, and other potential batch effects are often unavoidable in long-term studies and meta-analysis. In order to reduce the impact of batch effects on microarray data, Johnson, Rabinovic, and Li developed ComBat for use when combining batches of gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 21 publications
0
72
0
1
Order By: Relevance
“…We also analyzed the pooled data of HUVECs and human coronary artery endothelial cells after revising with ComBat analysis to eliminate the batch effects between the 2 cell types. 28 The ComBat analysis showed that a total of 1050 genes, including those of the VEGF signaling and focal adhesion pathways, were significantly altered by the LIPUS treatment ( Figure 3C; Table II in the online-only Data Supplement). The data analyzed by Ingenuity Pathway Analysis tools (Ingenuity Systems, Mountain View, CA) represent the possible involvements of focal adhesion pathway and its downstream signaling pathways ( Figure IIID in the online-only Data Supplement).…”
Section: Effects Of the Lipus Therapy On Signaling Pathways In Human mentioning
confidence: 99%
“…We also analyzed the pooled data of HUVECs and human coronary artery endothelial cells after revising with ComBat analysis to eliminate the batch effects between the 2 cell types. 28 The ComBat analysis showed that a total of 1050 genes, including those of the VEGF signaling and focal adhesion pathways, were significantly altered by the LIPUS treatment ( Figure 3C; Table II in the online-only Data Supplement). The data analyzed by Ingenuity Pathway Analysis tools (Ingenuity Systems, Mountain View, CA) represent the possible involvements of focal adhesion pathway and its downstream signaling pathways ( Figure IIID in the online-only Data Supplement).…”
Section: Effects Of the Lipus Therapy On Signaling Pathways In Human mentioning
confidence: 99%
“…Alignment of raw data was performed using Novoalign (http://novocraft.com/) on mouse miRNA sequences from mirBase. Quantification was performed using multiBamCov 44 46 and batch effects corrected by ComBat 43 . After batch correction, technical replicates were averaged for further analyses.…”
Section: Mirna-seqmentioning
confidence: 99%
“…Data were normalized using cqn 45 , which corrects for GC content and gene-length. A non-parametric version of Combat methodology 46 was used after cqn to correct for library-preparation effects.…”
Section: Rna-seqmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, such drift can significantly compromise the technical precision and signal stability in large-scale studies, where the data acquisition for several hundred to thousands of biological samples needs to be done in different analytical blocks (i.e. batches) over several weeks or even months 14,15 . In this case the largest variance in the dataset may be assigned to the batch effect or experimental run order, thus hindering the real biological difference and true functional signals, leading to data misinterpretation 14,16,17 .…”
Section: Introductionmentioning
confidence: 99%